Antioxidant homeostasis is disturbed in fetuses with leptin-resistant genotypes: A cross-sectional study - Pedro Gonzalez-Añover; Laura Torres-Rovira; Consolacion García-Contreras; Marta Vazquez-Gomez; Jose Luis Pesantez; Maria Victoria Sanz-Fernandez; Susana Astiz; Antonio Gonzalez-Bulnes (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Leptin resistance is associated with lower reproductive efficiency, with deficiencies in embryo viability and growth leading to low prolificacy and high incidence of intrauterine growth restriction. Objective: We aimed to investigate the underlying mechanisms of the leptin-resistance, evaluating the antioxidant homeostasis of leptin-resistant and lean swine fetuses. Materials and Methods: The study included 70 plasma samples from fetuses at day 62 of gestation (mid-pregnancy), from breeds with (Iberian breed; n=35) and without leptin resistance (25% Large White x 25% Landrace x 50% Pietrain; n=35). The antioxidant status of the plasma samples was determined by photoinduced chemiluminescence whilst systemic oxidative stress was assessed determining plasma hydrogen peroxide concentration by enzimoimmunoassay. Results: Plasma total antioxidant capacity was significantly lower in leptin-resistant fetuses (p=0.003), whilst systemic oxidative stress was increased (p=0.02). Conclusion: Our results indicate key differences in the antioxidant status in pregnancies affected by leptin resistance